ASUHAN KEBIDANAN PADA BAYI NY.S DENGAN BERAT BADAN LAHIR RENDAH DI PUSKESMAS CISEENG - Hanifah, Widyna; Djamilus, Fauzia (Jurnal Kesehatan Siliwangi, 2023)
Low Birth Weight (LBW) is a baby with a gestational period of less than 37 weeks with a weight appropriate to its gestational age (premature), a baby who experiences intrauterine growth retardation. According to data from the Ciseeng Health Center for January-February 2023, the incidence of LBW babies was 6 out of 77 live births (4.6%). The purpose is to be able to describe the results of midwifery care for Mrs. S with LBW. . Data collection techniques used were interviews, physical examination, observation, documentation study and literature study. Results of subjective data assessment: Mrs. S, 29 years old, 42 weeks pregnant, during pregnancy only made four irregular visits to antenatal care and experienced anemia. Objective data obtained was a baby born on February 21 2023 at 13.10 WIB crying strongly, active muscle tone, reddish skin, weight 2300 grams. The analysis obtained was that Mrs. S's baby had a low birth weight. The treatment given is to keep the baby warm by drying the baby's body, wearing a head covering and then doing IMD for 1 hour. The conclusion from the care provided to Mrs. S's baby is subjective data from a baby with a history of pregnancy with anemia.birth weight. It is recommended that mothers pay more attention to conditions in subsequent pregnancies and it is hoped that patients will continue to visit health facilities to check the growth and development of their babies and fulfill their immunization needs. Keywords: Midwifery Care, LBW